KETAKSAMAAN CHEBYSHEV DAN PERUMUMANNYA - Pangeran B.H.P; Hendra Gunawan (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2012)
We study Chebyshev’s Inequality and example of its application on the expectation of a continuous random variable. In addition, we also discussed the inequality on determinant form.